Limit analysis of annular footings acted upon by axisymmetric load - Kumar, B. Yaswanth; Kumar, Rajesh; Kumar, Veerendra (Journal of Structural Engineering, 2025)
This paper presents the analytical solutions for limit analysis of axisymmetric annular footings with axisymmetric loading. The proposed analysis provides a unified approach to calculate the collapse load for all types of collapse mechanisms whether partial or complete for an axisymmetric footing in contrast to that of yield line method which deals with complete collapse of the slab. Such footings with polar reinforcements are analyzed for uniform pressure distribution. Appropriate graphs for moment capacities are drawn. Region boundaries which help in deciding the type of failure the footing would undergo for a given set of dimensions are also presented which help as design aids.